Importance of factors determining the low health‐related quality of life in people presenting with a diabetic foot ulcer: the Eurodiale study. Issue 11 (15th July 2013) - Siersma, V.; Thorsen, H.; Holstein, P. E.; Kars, M.; Apelqvist, J.; Jude, E. B.; Piaggesi, A.; Bakker, K.; Edmonds, M.; Jirkovska, A.; Mauricio, D.; Ragnarson Tennvall, G.; et al.
Abstract Aim To identify the factors responsible for the low health‐related quality of life associated with foot ulcers and the relative importance of these factors. Methods A total of 1232 patients with a new foot ulcer, who presented at one of the 14 centres in 10 European countries participating in the Eurodiale study, were included in this cross‐sectional study. Patient and ulcer characteristics were obtained as well as results from the Euro‐Qol‐5D questionnaire, a health‐related quality of life instrument with five domains (mobility, self‐care, usual activities, pain/discomfort and anxiety/depression). To analyse the relative importance of comorbidities and ulcer‐ and patient‐related factors for health‐related quality of life, linear regression models were used to calculate the relative contributions of each factor to the fit (R2) of the model. Results Patients reported poor overall health‐related quality of life, with problems primarily in the mobility and pain/discomfort domains. Among the comorbidities, the inability to stand or walk without help was the most important determinant of decreased health‐related quality of life in all five domains. Among ulcer‐related factors, ulcer size, limb‐threatening ischaemia and elevated C‐reactive protein concentration also had high importance in all domains. The clinical diagnosis of infection, peripheral arterial disease and polyneuropathy were only important in the pain/discomfort domain. Conclusions The factors that determine health‐related quality of life are diverse and to an extent not disease‐specific. To improve health‐related quality of life, treatment should not only be focused on ulcer healing but a multifactorial approach by a specialized multidisciplinary team is also important.